Plasma catalytic non-oxidative methane conversion to hydrogen and value-added hydrocarbons on zeolite 13X. (15th June 2023) - Nguyen, Hoang M.; Gorky, Fnu; Guthrie, Shelby; Crawford, James M.; Carreon, Moises A.; Jasinski, Jacek B.; Carreon, Maria L.
Graphical abstract: Highlights: Pd-Ga/13X catalyst delivered the highest CH4 conversion and product yield compared to monometallic catalysts. Pd-Ga/13X converted 70 % CH4 to a H2 yield of 28 % and 23% of total hydrocarbons at a relatively low plasma power of 10 W. Energetic electrons played an important role in the activation and dissociation of C–H bonds in the gaseous plasma. Both energetic electrons, catalyst activity, and plasma-catalyst synergisms determined the final methane conversion performance for the plasma-catalyst process. Abstract: Non-thermal plasma has unfolded highly efficient, safe to operate novel routes for methane conversion to hydrogen. In this work, methane conversion is performed under atmospheric dielectric barrier discharge (DBD) plasma with and without 13X zeolite-based catalysts i.e., 13X, Ga/13X, Pd/13X, and Pd-Ga/13X. Experimental results indicate that the plasma catalytic process delivered almost twofold higher product yield than the plasma only route. The binary Pd-Ga catalyst possesses highest catalytic performance with about 40 % CH4 conversion at an input flowrate of 5 cm 3 min −1 and 2 W due to the formation of the Pd-Ga alloy, which acts as catalytic active centre for activating C–H bonds. Product yield can be tailored by the catalyst design where the bimetallic Pd-Ga/13X preferably favours the hydrocarbon formation while H2 is the dominant product obtained over the Pd/13X. The cleavage of C–H bonds of methane molecule over the plasma only route is mainly governed by energetic electrons in the gaseous phase the catalyst activity, and plasma-catalyst synergism play a significant role in the plasma catalysis process. The findings from this work provide significant insights into the methane activation for subsequent optimization of the methane conversion processes operated on floating production, storage, and offloading vessels (FPSOVs). Exploiting untapped offshore natural gas reserves, where conventional pipeline systems are less economical.